Analysis of Lead and Copper Concentrations in Mangrove Clams (Geloina erosa) and Sediments in The North Coast of Bengkalis Island - Gunova, M. Taufik; Amin, Bintal; Nursyirwani, Nursyirwani (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
This research was conducted in February-April 2021 by taking samples of mangrove clams (Geloina erosa) and sediment from Selat Baru and Teluk Pambang coastal area in Bantan District, Bengkalis Regency, Riau Province. The purpose of this study was to determine the concentration of heavy metals, namely Pb and Cu, in sediment and mangrove clams that are abundant in the studied area. The research method used is the survey method and samples were taken by means of the purposive sampling technique. Heavy metal concentrations were analyzed by using Atomic Absorption Spectrophotometer (AAS). The results showed that the concentrations of Pb and Cu in the mangrove clams and sediments in the studied area had not yet passed the threshold level. Pb and Cu concentrations found on clams were 0.0468 μg/g and 0.1043 μg/g respectively. Meanwhile, the concentration of Pb in the sediment was 0.10185 μg/g and Cu 0.3313 μg/g. Mangrove clams in the north coast of Bengkalis Island have the ability to accumulate Pb and Cu with a low ability (BCF<1). The maximum Tolerable Intake of the clams for humans with a bodyweight of 70 kg is 0.0983 kg/week (Lead) and 7.3010 kg/week for Copper.